Stylization of folklore images in the lyrics of Ibragim Yusupov - Zamira Ayimbetova (Zien Journals, 2023)
The study focuses on the stylization of folklore images in the lyrics of Ibragim Yusupov, a prominent poet from Karakalpakstan. The analysis is based on his selected works, which demonstrate his unique approach to the use of traditional motifs and symbols in contemporary poetry. The research aims to explore the ways in which Yusupov reinterprets and transforms the cultural heritage of his region, creating a new poetic language that reflects both the continuity and innovation in Karakalpakstan folklore
Keywords: folklorism; assimilation; stylization